Role of renal biomarkers as predictors of acute kidney injury in cardiac surgery. (February 2014) - Ghatanatti, Ravi; Teli, Anita; Tirkey, Sundeep Sanjivan; Bhattacharya, Subhankar; Sengupta, Gautam; Mondal, Ansuman
Cardiac surgery is unique in using cardiopulmonary bypass in various clinical scenarios. Injury of vital organs is unavoidable in the perioperative period. Acute kidney injury is a consequence of the systemic inflammatory response after bypass, emboli, ischemia, and low cardiac output states, reportedly occurring in 30%–40% of open heart surgeries. Acute kidney injury is associated with increased morbidity, mortality, and cost. Many preventive measures (off-pump procedures, decreased crossclamp time, pulsatile flow, adequate hydration) are taken in the perioperative period to avoid organ injury, but in vain. Traditionally, blood urea, serum creatinine, and creatinine clearance rate were applied for prediction of acute kidney injury. The recent emergence of biomarkers such as neutrophil gelatinase-associated lipocalin, cystatin C, liver-type fatty acid binding protein, interleukin-18, kidney injury molecule-1, and tetrahydrobiopterin have helped in detecting acute kidney injury long before the rise of serum creatinine. These biomarkers can also be used as tools for predicting therapeutic effects in acute kidney injury and for monitoring drug toxicity. This review consolidates the knowledge of biomarkers and their application in acute kidney injury management.